Multimodality local consolidative treatment versus conventional care of advanced lung cancer after first-line systemic anti-cancer treatment: study protocol for the RAMON multicentre randomised controlled trial with an internal pilot - Matthew Evison; Tim Batchelor; Chris A Rogers; Sarah Baos; Elizabeth A Stokes; Rosie Harris; Eric Lim; Chloe Beard; Janette Rawlinson; Nicola Mills; John Conibear; Paulo De Sousa; et al. (BMJ Open)
Introduction Lung cancer is the most common cause of cancer death worldwide and most patients present with extensive disease. One-year survival is improving but remains low (37%) despite novel systemic anti-cancer treatments forming the current standard of care. Although new therapies improve survival, most patients have residual disease after treatment, and little is known on how best to manage it. Therefore, residual disease management varies across the UK, with some patients receiving only maintenance systemic anti-cancer treatment while others receive local consolidative treatment (LCT), alongside maintenance systemic anti-cancer treatment. LCT can be a combination of surgery, radiotherapy and/or ablation to remove all remaining cancer within the lung and throughout the body. This is intensive, expensive and impacts quality of life, but we do not know if it results in better survival, nor the extent of impact on quality of life and what the cost might be for healthcare providers. The RAMON study (RAdical Management Of Advanced Non-small cell lung cancer) will evaluate the acceptability, effectiveness and cost-effectiveness of LCT versus no LCT after first-line systemic treatment for advanced lung cancer.Methods and analysis RAMON is a pragmatic open multicentre, parallel group, superiority randomised controlled trial. We aim to recruit 244 patients aged 18 years and over with advanced non-small-cell lung cancer from 40 UK NHS hospitals. Participants will be randomised in a 1:1 ratio to receive LCT alongside maintenance treatment, or maintenance treatment alone. LCT will be tailored to each patient’s specific disease sites. Participants will be followed up for a minimum of 2 years. The primary outcome is overall survival from randomisation.Ethics and dissemination The West of Scotland Research Ethics Committee (22/WS/0121) gave ethical approval in August 2022 and the Health Research Authority in September 2022. Participants will provide written informed consent before participating in the study. Findings will be presented at international meetings, in peer-reviewed publications, through patient organisations and notifications to patients.Trial registration number ISRCTN11613852.